CD5L induces inflammation and survival in RA-FLS through ERK1/2 MAPK pathway - Huiqing Yang; Yan Luo; Xiaofei Lai (Taylor & Francis Group, 2024)
AbstractObjective To explore the effect of CD5-like molecule (CD5L) on rheumatoid arthritis (RA) fibroblast-like synoviocytes (RA-FLS) and the relative molecular mechanism of CD5L in it.Methods Recombinant protein CD5L was used to stimulate the cultured RA-FLS cells. The inflammation-related cytokines were determined by real time-polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA). The signal molecules and apoptosis-related molecules were detected by western blot assay (WB), and cell counting kit-8 (CCK-8) was used to detect the proliferation.Results CD5L can increase the production of IL-6, IL-8, and TNF-α and this effect can be inhibited by signal pathway inhibitor. At the same time, CD5L activated ERK1/2 MAPK signal, inhibitor treatment can weaken the intensity of phosphorylation. In addition, CD5L can enhance the proliferation ability of RA-FLS.Conclusion CD5L induces the production of inflammatory cytokines in RA-FLS through the ERK1/2 MAPK pathway and increases cell survival.